2014
DOI: 10.20467/1091-5710.18.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Caring Theory into Personal and Professional Nursing Practice to Improve Perception of Care

Abstract: A one-day Watson’s caring theory educational seminar was presented to 10 staff nurses from a community hospital with the intent to improve patients’ perception of care. A quasi-experimental design was employed, using descriptive statistics and t tests to compare measures of perceptions of care pre and post the educational session. A statistically significant increase in nurse’s confidence in caring attitudes and behaviors was found as measured by the caring nurse patient interaction scale nurse version (CNPI-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Cossette et al did so to compare RN and NS in terms of feeling of competence of. In their work, Desmond et al (2014) demonstrated with the help of the CNPI-70 that a CPD activity increased the feeling of competence of participants regarding caring. In our research, the NS felt just as competent as the RN did regarding "humanistic care" and "comforting care," which suggests that whether the basic nursing curriculum is completed or not makes no difference.…”
Section: Feeling Of Competence Regarding Caring In Nursing Professimentioning
confidence: 99%
“…Cossette et al did so to compare RN and NS in terms of feeling of competence of. In their work, Desmond et al (2014) demonstrated with the help of the CNPI-70 that a CPD activity increased the feeling of competence of participants regarding caring. In our research, the NS felt just as competent as the RN did regarding "humanistic care" and "comforting care," which suggests that whether the basic nursing curriculum is completed or not makes no difference.…”
Section: Feeling Of Competence Regarding Caring In Nursing Professimentioning
confidence: 99%